Comparison of absorption–dispersion and optical bistability behaviors between open and closed four-level tripod atomic systems. (21st July 2015) - Karimi, R.; Asadpour, S. H.; Batebi, S.; Rahimpour Soleimani, H.
Abstract: In this paper we investigate the optical properties of an open four-level tripod atomic system driven by an elliptically polarized probe field and compare its properties with the corresponding closed system. Our results reveal that absorption, dispersion, group velocity, and optical bistability of the probe field can be manipulated by adjusting the phase difference between the two circularly polarized components of a single coherent field and cavity parameters, i.e., the atomic exit rate from cavity and atomic injection rates.